Right answer is (b) Bt(w,v)+Bv(w,v)-B̅p(w,P)=l(w) and –Bp(w3, v)=0

Best explanation: The problem described by weak forms of viscous fluids flow equations can be restated as a variational problem of finding (vx, vy, P) such that Bt(w,v)+Bv(w,v)-B̅p(w,P)=l(w) and –Bp(w3, v)=0 holds for all weight functions (w1, w2, w3) and t>0. Here, we have used the notation w=\(\begin{Bmatrix}w_1\\w_2\end{Bmatrix}, \)v=\(\begin{Bmatrix}v_x\\v_y\end{Bmatrix},\) f=\(\begin{Bmatrix}f_x\\f_y\end{Bmatrix}\) and t=\(\begin{Bmatrix}t_x\\t_y\end{Bmatrix}\).